Deep-play: developing TPACK for 21st century teachers. (1st January 2011) - Koehler, Matthew J.; Mishra, Punya; Bouck, Emily C.; DeSchryver, Michael; Kereluik, Kristen; Shin, Tae Seob; Wolf, Leigh Graves
A key complication facing teachers who seek to integrate technology in their teaching is the fact that most technologies are not designed for educational purposes. Making a tool an educational technology requires creative input from the teacher to re-design, or maybe even subvert the original intentions of the designer. The learning technology by design (LT/D) framework has been proposed as being an effective instructional technique to develop deeper understanding of technological pedagogical content knowledge. In this paper we expand our description of the LT/D technique to develop what we call a deep-play model for teacher professional development. The deep-play model integrates: a pedagogy for key 21st century learning skills b content that cuts across disciplines with trans-disciplinary cognitive tools c technology by the creative repurposing of tools for pedagogical purposes.